THE UTILIZATION OF BEHAVIORAL FINANCE MODELS IN ANALYZING INVESTMENT DECISIONS - Prayoga, Bagas Adi; Hariyanto, Wiwit (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study analyzes the impact of student financial behavior on investment decisions using a Behavioral Finance model. Method: Data were collected throgh interviews and observations with a descriptive qualitative approach. Results: The findings show that financial behaviors, such as adherence to payment schedules, budgeting and price comparison, significantly influence investment choices. Emotiona and psycological factors, like status quo bias, risk aversion, and overconfidance, also affect decision-making, often leading to suboptimal outcomes. Interviews confirm that these factors frequently hinder rational choices. Howefer, the study’s limitations include sample representation and generalizabillity. Novelty: This research contributes to understanding Behavioral Finance in Investment Decisions and highlights the need for better financial education.